KUALITAS SPERMA SAPI ANGUS DALAM PENGENCER CITRATE-KUNING TELUR YANG DITAMBAHKAN SARI BUAH TOMAT (Sperm quality of angus bulls in citrate - egg yolk extender added tomato juice) - Valerianus L. Janggur; Thomas Mata Hine; Petrus Kune (JURNAL NUKLEUS PETERNAKAN, 2023)
Preservation is a technology created to keep sperm quality over a specific time period, which is subsequently used for artificial insemination. Attempts have been made to reduce the loss of sperm quality during storage by diluting the sperm with materials containing various nutritional components required by sperm to preserve motility and vitality during storage. This study aimed to analyze the impact of adding tomato juice (TJ) to citrate–egg yolk (CEG) diluent on the sperm quality of Angus bulls. One three-year-old angus bull was collected using an artificial vagina, and good quality sperm was preserved in CEG diluent with various levels of TJ added: 0, 1, 2, and 3% for treatments P0, P1, P2, and P3 sequentially. After dilution, the sperm were stored in the refrigerator with a temperature range of 3-5oC. Sperm quality was evaluated every 24 hours until motility reaches 40%. The results of the study up to the fifth day of storage showed significant differences (P<0.05) in the variables of sperm motility, viability, and survival, but there were no significant differences in the variable of sperm abnormalities (P>0.05) between the P2 and P3 with control. The following sperm quality comparisons were made in the P3 vs. control treatment: motility (50.00 vs. 36.50%), viability (54.84 vs. 47.35%), abnormality (7.35 vs. 7.07%), and survival (5.83 vs. 4.50 days). The study concluded that adding 2-3% TJ in the CEG diluent could sustain the sperm quality of Angus bulls.